Analisis Kekuatan Bending dan Kekuatan Impact Komposit Epoxy Diperkuat Serat Pelepah Lontar - Saduk, Melsiani Rosdiani Fillipin; Niron, Fransisko Piri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
Natural fibers have been considered as reinforcement in composite materials which is environmentally friendly fiber instead of fiberglass. The use of natural fibers in the composite material is currently growing, along with the increasing use of such materials are widespread ranging from household appliances and industrial sector. The aim of this research was to determine the impact strength and bending strength of lontar fiber composite. The production method of this composite is hand lay-up with random fiber orientation (randomly oriented fiber discontinuous). The compositesÂ were produced with a variety of fiber volume fraction of 10%, 15%, 20%, 25% and 30 %. The bending strength of lontar fiber composite 140.235 MPa and modulus of elasticity of 4440 Mpa were obtained. The impact strength of lontar fiber composite and fiberglass were 0.439J/mm2 and 0.8333 J / mm2 respectively.